EU Policy Towards China: Regulations for 5G Infrastructure Vendors (Economic and Political Thought, 2023)
The process of building networks for the provision of telecommunicationsservices using 5G technology has been ongoing for several years, and will beused in various sectors of the newest industries, as well as in state structures.In the world, infrastructure for 5G technology is provided by only a fewmanufacturers. In Europe, Nokia and Ericsson, and outside Europe, ChineseHuawei and ZTE and Korean Samsung. In the last few years, the issue ofsupplying equipment for the construction of 5G infrastructure from Chinahas become the subject of a heated discussion between the US and China.From the US side, doubts are raised as to whether this equipment ensuresthe security of use of 5G services by citizens and entities around the world,including those in the European Union (“EU”), due to the possible influenceon their manufacturers by the Chinese government. The discussion betweenthe US and China resulted in the adoption of a number of recommendationsin the EU in the field of 5G cybersecurity, including Cybersecurity of5G networks EU Toolbox of risk mitigating measures (“5G Toolbox”). Specificrecommendations have been formulated in the 5G Toolbox regarding theso-called High Risk Vendors (“HRV”). Based on these recommendations,some EU countries have introduced national regulations regarding HRV.Due to the different pace of adoption of these regulations in individual EUcountries and the different ways of implementing these regulations and enforcingalready implemented provisions, demands are being made to adopta uniform regulation in the EU in the field of HRV, which would apply to allEU countries. The article analyzes whether it is justified to adopt uniformEU regulations in this regard at the current stage of the adopted regulationsregarding HRV.
Keywords: high risk vendors, 5G Toolbox, cybersecurity, telecommunications infrastructure